AB0482 Dual Neutralization of TNF-α and CXCL10 with Bispecific IGG (IGG-SCFV, MSK–101) is Efficacious in Human TNF Transgenic Mice and LPS-Induced Bone Resorption Model. (9th June 2015) - Park, S.; Yoo, H.J.; Choi, J.Y.; Kang, H.S.; Park, B.C.; Park, Y.W.; Kim, S.Y.; Shin, K.C.; Lee, E.Y.; Lee, E.B.; Song, Y.W.
Abstract : Background: Tumor necrosis factor-α (TNF-α) is a pivotal cytokine which plays a crucial role in the pathogenesis of rheumatoid arthritis (RA), and monoclonal antibodies targeting TNF-α are widely used in the clinic. However, there is unmet need for non-responders to TNF inhibitor. CXCL10 is a chemokine that is increased in the serum and synovial fluid of RA and important in migration of pro-inflammatory cells and fibroblasts and bone destruction in RA. Anti-CXCL10 monoclonal antibody was reported to be efficacious in RA and ulcerative colitis clinical trial. Objectives: We developed a bispecific antibody of IgG-based format (IgG-scFv, MSK-101) against TNF-α and CXCL10 and evaluated dual neutralization effect of the antibody in in vitro and in vivo model of RA. Methods: Binding affinity of MSK–101 for TNF-α and CXCL10 was measure by ELISA. In vitro neutralizing ability of MSK–101 was analyzed in a TNF-α sensitive WEHI164 cell line. We performed migration assay of Jurket cell using transwell system and an inhibitory assay of osteoclast differentiation to demonstrate CXCL10 blocking effect. We analyzed arthritis scores and histological damage in human TNF transgenic mice after treatment with vehicle, MSK–101 (13.8 mg/kg) or TNF-α blocker (10 mg/kg) twice a week for 7 weeks beginning at 3.5 weeks of age. LPS-induced bone resorption model was utilized to test the antibody effect on osteoclast differentiation and bone resorption using a micro-CT scan. Results: The binding affinity of MSK–101 for TNF-α and CXCL10 was 0.03 nM and 0.47 nM compared with. TNF-α blocker for TNF-α 0.07 nM. TNF-α mediated toxicity was neutralized (EC50) by MSK–101 at concentration of 12.09 ng/ml and TNF-α blocker at 24.19 ng/ml. CXCL10-induced migration of Jurket cell was significantly reduced by MSK–101 (p=0.008). Moreover, TNF-α- and CXCL10-induced osteoclast differentiation was inhibited by MSK-101 (68% vs control, p=0.001), but not by TNF-α blocker (41% vs control, p>0.05) in T cell/monocyte co-culture system. Mean arthritis scores and histological scores were significantly lower in MSK-101 group and TNF-α blocker group than vehicle group in human TNF transgenic mice (p<0.001, p<0.001, respectively in each group). MSK–101 significantly reduced bone resorption compared to vehicle (48.79%, p=0.042) in LPS-induced bone resorption model, but TNF-α blocker did not (8.48%, p=0.73). Conclusions: MSK–101, bispecific IgG (IgG-scFv) is a novel antibody targeting TNF-α and CXCL10. MSK–101 binds to TNF-α and CXCL10 with high affinity. Dual neutralization by bispecific IgG (IgG-scFv) was efficacious in a preclinical model of RA. References: Tim Bongartz et al. 2006 JAMA. 295(19):2275-2285. R. Hanaoka et al. 2003 Arthritis Res Ther, pp. R74–R81. E.Y. Lee et al. 2013. Autoimmun Rev, 12, pp. 554–557. Acknowledgements: This work was supported by NRF (F01-2009-000-10196-0), and partly by the MKE/KEIT R&D Program (grant number 10035615). Disclosure of Interest: None declared